2019
DOI: 10.1053/j.gastro.2018.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Acting Antiviral Therapy for HCV Infection Is Associated With a Reduced Risk of Cardiovascular Disease Events

Abstract: is associated with an increased risk of cardiovascular disease (CVD) events. It is not clear whether treatment with directacting antiviral (DAA) agents affects risk of CVD. METHODS:We searched the Electronically Retrieved Cohort of HCV-Infected Veterans database for patients with chronic HCV infection (n ¼ 242,680) and identified patients who had been treated with a pegylated interferon and ribavirin regimen (n ¼ 4436) or a DAA-containing regimen (n ¼ 12,667). Treated patients were matched for age, race, sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
118
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 39 publications
9
118
3
1
Order By: Relevance
“…45,46 The beneficial effect of a reduction in the risk of cardiovascular events has been observed to be limited in patients with severe fibrosis. 43 Coincidently, we observed that the SUA decrements were also less evident in cases of severe fibrosis. The role of SUA as a trigger or bystander, in terms of cardiovascular events in CHC patients, awaits future clarification.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…45,46 The beneficial effect of a reduction in the risk of cardiovascular events has been observed to be limited in patients with severe fibrosis. 43 Coincidently, we observed that the SUA decrements were also less evident in cases of severe fibrosis. The role of SUA as a trigger or bystander, in terms of cardiovascular events in CHC patients, awaits future clarification.…”
Section: Discussionsupporting
confidence: 56%
“…This raises the issue as to whether SUA decrements reduce the risk of cardiovascular events and all‐cause mortality, which requires further exploration and discussion . The beneficial effect of a reduction in the risk of cardiovascular events has been observed to be limited in patients with severe fibrosis . Coincidently, we observed that the SUA decrements were also less evident in cases of severe fibrosis.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…A recent retrospective, a case‐controlled study involved 4436 pegylated interferon/ribavirin‐treated and 12 667 DAA‐treated CHC patients. Treatment with pegylated interferon and ribavirin (hazard ratio, 0.78; 95% CI, 0.71‐0.85) or a DAA regimen (0.57; 95% CI, 0.51‐0.65) was associated with a significantly lower risk of a cardiovascular event than that associated with no treatment . However, findings regarding vascular parameters following SVR that is achieved by DAA are inconsistent.…”
Section: Chronic Hepatitis Viral Infection and Arteriosclerosismentioning
confidence: 99%